2017
DOI: 10.1021/acs.jpca.7b00893
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects on the Nuclear Spin Isomer Conversion of H2O

Abstract: The mechanism for interconversion between the nuclear spin isomers (NSI) of HO remains shrouded in uncertainties. The temperature dependence displayed by NSI interconversion rates for HO isolated in an argon matrix provides evidence that confinement effects are responsible for the dramatic increase in their kinetics with respect to the gas phase, providing new pathways for o-HO↔p-HO conversion in endohedral compounds. This reveals intramolecular aspects of the interconversion mechanism which may improve method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Getting experimental data to deal with nuclear spin effects is crucial to simulate and understand nuclear spin population distributions. The nuclear spin conversion mechanism has been investigated to estimate the lifetime conservation of a potential thermal disequilibrium (Fillion et al 2012;Cacciani et al 2012;Turgeon et al 2017), as well as the effect of adsorption and desorption on the OPR (Hama et al 2016). Furthermore selective reaction or formation of water nuclear spin isomers could also be taken into account by the models (Kilaj et al 2018).…”
Section: Grain Surface Chemistrymentioning
confidence: 99%
“…Getting experimental data to deal with nuclear spin effects is crucial to simulate and understand nuclear spin population distributions. The nuclear spin conversion mechanism has been investigated to estimate the lifetime conservation of a potential thermal disequilibrium (Fillion et al 2012;Cacciani et al 2012;Turgeon et al 2017), as well as the effect of adsorption and desorption on the OPR (Hama et al 2016). Furthermore selective reaction or formation of water nuclear spin isomers could also be taken into account by the models (Kilaj et al 2018).…”
Section: Grain Surface Chemistrymentioning
confidence: 99%
“…On the other hand, if molecules were returned to the gas phase by a mechanism that is intrinsically faster than the cosmic ray-induced desorption processes considered here, the molecular column densities might become dependent on chemical reactions on the surfaces of grains. Furthermore, surface processes, and especially those possibly involved in spin conversion, are still poorly constrained (Turgeon et al 2017), and the impact of such processes on the observed gas-phase ortho:para ratios is difficult to anticipate. Finally, we note that the agreement with the observations is obtained at densities for which the main contribution to the column density of ammonia and deuterated analogs comes from the free-falling core, before freeze-out begins to be dominant.…”
Section: Total Column Densitiesmentioning
confidence: 99%
“…This analysis predicts that the A ″ rotational constant is ∼42% of the gas-phase value, and therefore the population of the para nuclear spin isomer at equilibrium at 1.7 K is significantly greater than what is predicted using the gas-phase rotational constants. Given that we measure an equilibrium POR value of ∼0.17 at 1.7 K, the approximate temperature where all the experiments were conducted, this implies that the elementary rate constants for the reversible first-order NSC kinetics are significantly different from the measured effective rate constant . We can use the measured k eff and POR (1.7(1) K, t = ∞) for five experiments (Experiment 3 was discarded) to determine k p→o = 3.00(9) × 10 –3 min –1 and k o→p = 4.4(11) × 10 –4 min –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Given that we measure an equilibrium POR value of ~0.15 at 1.7 K, the approximate temperature where all the experiments were conducted, this implies that the elementary rate constants for the reversible first-order NSC kinetics are significantly different from the measured effective rate constant. 56 We can use the measured k eff and POR(1.7(1) K, t=∞) for five experiments (Expt. 3 was discarded) to determine k p → o = 3.00(9) x 10 -3 min -1 and k o → p = 4.4 (11) x 10 -4 min -1 .…”
Section: C Measuring the Para-to-ortho Ratio For Propyne In Solid Pmentioning
confidence: 99%